IMPLEMENTASI TEKNIK BEHAVIORAL REHEARSAL UNTUK MENINGKATKAN EMPATI MAHASANTRI PADA MASA KARANTINA AL- QUR’AN DI PONDOK PESANTREN IBNU KATSIR 2 JEMBER - Isnafiyah Nur Adzkiyah; Imaratul Ulwiyah; Wahid Suharmawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study discusses the effectiveness of behavioral rehearsal techniques to increase empathy of students during the Al-Qur'an quarantine period at the Ibnu Katsir 2 Islamic boarding school in Jember. This type of research is quantitative research. The population is all students of the 2021 batch of the Ibnu Katsir 2 Islamic boarding school in Jember with a sample of 5 students. Data collection methods using observation, interviews, questionnaires. Before being distributed, the questionnaire was tested for validation and reliability. The data analysis technique used was the Wilcoxon Match Pairs Test. The results of the study are: there is an effectiveness of behavioral rehearsal techniques to increase empathy of students during the Al-Qur'an quarantine period at the Ibnu Katsir 2 Islamic boarding school in Jember. This is evidenced by the results of the average calculation of the pretest and posttest scores, which showed an increase in empathy of students. In the pretest, the average score was 133 and the average score in the first posttest was 141.8 with a difference of 8.8 score points, the second posttest was 150.6 with a difference of 8.8 score points, the third posttest was 160.4 with a difference of 9.8 score points and the last posttest was 167.2 with a difference of 6.8 score points. And obtained in the data analysis using the Wilcoxon Match Pairs Test, the Asymp. Sig. (2-tailed) value of 0.042 which is smaller than 0.05, it can be interpreted that there is a significant difference in the level of empathy of students for the pretest and posttest (hypothesis accepted). It can be concluded that there is an effectiveness of the behavioral rehearsal technique to increase empathy of students during the Al-Qur'an quarantine period at the Ibnu Katsir 2 Islamic boarding school in Jember.